Artificial intelligence‐assisted fatigue fracture recognition based on morphing and fully convolutional networks. Issue 6 (6th April 2022) - Lyu, Yetao; Yang, Zi; Liang, Hao; Zhang, Beini; Ge, Ming; Liu, Rui; Zhang, Zhefeng; Yang, Haokun
Abstract: Fatigue fracture is one of the most common metallic component failure cases in manufacturing industries. The observation on fractography can provide direct evidence for failure analysis. In this study, an image semantic segmentation method based on fully convolutional networks (FCNs) was proposed to figure out the boundary between fatigue crack propagation and fast fracture regions from optical microscope (OM) fractography images. Furthermore, a novel morphing‐based data augmentation method was adopted to enable few‐shot learning of sample images. The proposed framework can successfully segment two categories, namely, the crack propagation and fast fracture regions, thus differentiating the boundary of two regions in one image. This artificial intelligence (AI)‐assisted fatigue analysis architecture can complete the failure analysis procedure in 0.5 s and prove the feasibility of fatigue failure analysis. The segmentation accuracy of self‐developed network achieves 95.4% for the fatigue crack propagation region, as well as 97.2% for the fast fracture region. Not only for semantic segmentation DNN, we also prove that our novel data augmentation method can applied at the instance segmentation DNN, such as mask regional convolutional neural network (mask R‐CNN), one state‐of‐the‐art deep learning network for instance segmentation, to achieve similar accuracy. Highlights: Artificial intelligence differentiates crack propagation and fast fracture regions. Morphing method generates more fatigue images based on limited resources. Few‐shot learning verifies at FCN‐based image segmentation algorithm with >97% accuracy.